PEDAGOGICAL SYSTEM AS A BASIS OF DEVELOPMENT OF STUDENTS' PERSONAL MATURITY - Olena Dysa (Alfred Nobel University Publisher, 2019)
The article dwells on the problem of students' personal development during their study at university. Each university is characterized by the definite pedagogical system that meets the requirements of law, social demands and the main directions of education development in Ukraine. Besides that, this system has its own ideas, purposes, tasks and vision for the future specialists' nurture. The pedagogical system of university is a combination of components that are interrelated and complement each other and have a definite hierarchical and structural unity. These components include aims, learning information, means of pedagogical communication among students and teachers. More than that, the pedagogical system of university is proved to be a basis for the development of students' personal maturity. It is the pedagogical system where the students' value orientations, moral principles and responsibility are formed. The pedagogical system at classical university varies from the one at university with specific conditions; consequently, it has a different impact on students' personal maturity development. Youth is regarded as a sensitive period for the formation of such characteristics as self-conscience, value orientations, and personal maturity as well as other things that have a great impact on the future specialists' professional development. The research results have shown that there is a discrepancy between the levels of personal maturity manifestation in students and cadets. The reasons for such a discrepancy are considered and analysed in the article. It is stated that a number of factors such as strict regulation, peculiarities of professional training, living conditions hinder the personal maturity development in cadets. The pedagogical system at university with specific conditions deliberately restricts cadets from spontaneous communication and external torrent of information in order to nurture and develop the professional qualities, i.e. discipline, individual responsibility and social responsibility, tolerance, resilience, as well as stamina to physical and psychological pressure, which are vitally important to the profession of a police officer.